A leaf extract of harrisonia abyssinica ameliorates neurobehavioral, histological and biochemical changes in the hippocampus of rats with aluminum chloride-induced Alzheimer’s disease - Anwar, Hend Mohamed; Georgy, Gehan S.; Hamad, Sherin Ramadan; Badr, Wafaa K.; El Raey, Mohamed A.; Abdelfattah, Mohamed A. O.; Wink, Michael; Sobeh, Mansour (Antioxidants, 2021)
Aluminum (Al) is an omnipresent mineral element in the environment. The brain is a central target of Al toxicity, being highly susceptible to oxidative damage. Therefore, recognition of drugs or natural products that guard against Al-mediated neuronal cell death is a powerful strategy for prevention and treatment of neurodegenerative disorders. This work aimed to explore the potential of a leaf extract from Harrisonia abyssinica to modulate the neurobehavioral, biochemical and histopathological activities induced experimentally by Al in vivo. Rats subjected to Al treatment displayed a reduction in learning and memory performance in a passive avoidance test accompanied by a decrease in the hippocampal monoamine and glutamate levels in addition to suppression of Bcl2 expression. Moreover, malondialdehyde (MDA), inflammatory markers (TNF-α, IL-1β), apoptotic markers (caspase-3 and expression of Bax) and extracellular regulated kinase (ERK1/2) levels were elevated along with acetylcholinesterase (AChE) activity, histological changes and marked deposition of amyloid β plaques in the hippocampus region of the brain tissues being observed in Al-treated animals. Concomitant administration of the high dose of H. abyssinica (200 mg/kg b.w.) restored nearly normal levels of all parameters measured, rather than the low dose (100 mg/kg b.w.), an effect that was comparable to the reference drug (rivastigmine). Molecular docking revealed the appropriate potential of the extract components to block the active site of AChE and ERK2. In conclusion, H. abyssinica leaf extract conferred neuroprotection against Al-induced neurotoxic effects, most likely due to its high phenolic and flavonoid content.